RECONSTRUCTING THE THINKING PROCESS OF MIDWIFERY CARE MANAGEMENT: AN ADDIE STUDY - J.M Metha; Juli Oktalia; Panca Desristanto (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Midwifery management process has been used as a guideline in clinical learning in midwifery. However, the management process that is used until currently has still been literally adopted from foreign sources which are not necessarily compatible with the understanding of most student midwives in Indonesia. Purpose: this ADDIE study was therefore intended to formulate steps in the thinking process of clinical midwifery care. From this series of research steps, Nine Steps of J.M. Metha had been successfully composed. Methods:This ADDIE (Analyze, Design, Develop, Implement, Evaluate) study was to formulate a clinical management mindset in midwifery. In the ‘develop’ section, R&D was used to create a product that could be used, for example, in the clinical learning of student midwives. In the ‘implement’ part, snow-ball sampling was used to extract the same anticipated data from the increasing number of participants. Finally, through FGD, participants’ opinions, which were selected from 3 people because of data saturation, were analyzed using a phenomenological approach to see the phenomena that existed in the use of the created products. Results: The Nine Steps of J.M. Metha were formulated, i.e., See who comes, Listen to the client, Examine the client, Asses the client’s condition, Inform the client about their condition, Plan actions for care, Implement care having planned, Evaluate the care having implemented, and Return to number 1. Based on the opinions of the respondents, these nine steps had already resembled the real midwifery sequences in daily practices. It is then necessary to disseminate this simple, easy to apply midwifery thinking process for the sake of better quality of student midwives and midwifery practitioners. Conclusion: These Nine Steps of J.M. Metha is likely to be suitable for use on the thinking process for midwifery care measures. A further study is therefore recommended with a larger scope of place and participants.